A STUDY ON TALENT ACQUISITION AMONG HR PROFESSIONALS WORKING IN VARIOUS IT SERVICES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many successful organizations realize their employees as their greatest asset. Therefore, mostHRs within the organization must recruit valuable candidates for the organization. The mainpurpose of the research is to research the activities of the sources of recruitment, performanceappraisal, and employee retention activities taken by the talent acquisition team within thecase of primary data, a structured questionnaire was prepared to know the importance ofTalent Acquisition activities, which might be qualitative data, and send across 60 respondentsrandomly from all the HRs working in various IT services. In secondary data to assess theimportance of sourcing the candidates, evaluation of Performance appraisal, EmployeeRetention activities and Employers mindset about Experience. The responses that we gotfrom the varied HRs are collected and that we had taken out the results through percentageanalysis, Correlation Tests, Regression Tests and Chi-Square Tests during which all the testshad been wiped out SPSS tools. Through these tests, we had some findings on the TalentAcquisition Activities of HRs working in various IT Sectors